Establishment of Chinese Hamster Ovary Cell Line Development and Engineering Platforms Using CRISPR/Cas9 and Recombinase-mediated Cassette Exchange - 신성욱 (The Graduate School, Ajou University, 2024)
Developing recombinant Chinese hamster ovary (CHO) cell lines via random integration (RI) is a labor-intensive and time-consuming process, limiting the large- scale production of biopharmaceuticals. Site-specific integration (SSI) is gaining attention as a next-generation method for cell line development (CLD). However, the application of SSI is constrained by low homology-directed repair pathway in CHO cells. Therefore, improving SSI efficiency is crucial for achieving streamlined and predictable CHO CLD. In this study, I established efficient SSI strategies for the (multiple) integration of transgene(s) using clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9). The biopharmaceutical market is rapidly growing, particularly with the advent of novel, but complex therapeutics such as bispecific antibodies. These proteins are often difficult-to-express (DTE) using current CLD methods because they can induce stress in the protein synthesis and secretion pathways, leading to apoptosis. To address these intracellular bottlenecks, substantial cell engineering is necessary to develop advanced CHO factories. Successful mammalian cell engineering requires precise control over gene expression in both quantitative and timely manner, depending on target genes. However, traditional methods, including transient expression or RI, lack precision and sustainability. Therefore, the development of reliable platforms that overcome these limitations is highly valuable in the field of mammalian synthetic biology. In this study, I developed a streamlined doxycycline-inducible CLD platform that enables precise and sustainable control of various effector genes through CRISPR/Cas9 and recombinase-mediated cassette exchange (RMCE). Case studies highlighting the effectiveness and applicability of this platform are presented. Another critical aspect of successful mammalian cell engineering is the appropriate engineering target selection depending on the specific contexts (e.g. expression host, therapeutic proteins). However, targets identified through knowledge- or omics/prediction-based approaches, may not always be reproducible and effective, due to the incomplete existing data and varying engineering contexts. In this study, I conducted RMCE-based genome-scale CRISPR knockout (KO) screening in two CHO cell lines to understand genetic functions and unveil novel targets. By comparing guide RNA distributions in pooled libraries from next- generation sequencing (NGS) data, I identified core and conditional essential genes, as well as candidate screen hits responsible for efficient biomanufacturing. I demonstrated the robustness and reproducibility of the obtained NGS data through technical validations and target gene validation, highlighting their potential use in diverse functional genomics applications, such as DTE protein production. Collectively, the established CHO CLD and engineering platforms using CRISPR/Cas9 and RMCE which include multiple SSI, reliable gene expression control, and genome-wide KO/functional genomics would contribute to improve productivity of recombinant cell lines and accelerate candidate drug screening and large-scale production, addressing the increasing unmet medical needs.|무작위적 유전자 삽입을 사용한 재조합 동물세포주 개발은 많은 시간과 노동이 필요하며, 바이오 의약품의 대량생산에 한계를 있음을 보여주었다. 이에 대한 대안으로, 위치 특이적 유전자 삽입을 기반으로 한 세포주 개발이 차세대 방법으로 주목받고 있지만, 초세포에서의 낮은 상동 재조합 효율로 인해 실제 적용에 여러 제약이 따랐다. 따라서, 위치 특이적 유전자 삽입 효율을 개선함으로써 효율적이고 예측 가능한 초세포 주 개발이 가능할 것으로 기대된다. 본 연구에서는 clustered regularly interspaced short palindromic repeats (CRISR)/CRISPR-associated protein 9 (Cas9)을 기반으로 한 (다중) 위치 특이적 외래유전자 삽입 기술을 확립하였다. 빠르게 성장하는 바이오 의약품 시장에서, 이중 특이항체와 같은 구조가 점점 더 복잡한 후보 신약들이 등장하고 있다. 이러한 단백질들은 기존의 플랫폼을 사용하여 생산하기 어려운 난발현 단백질로 분류되며, 그 특성에 따라 단백질 합성 및 분비 경로에서 스트레스를 유발하고, 세포 사멸 초래하는 것으로 알려져 있다. 이러한 세포 내부에서 발생하는 문제를 해결하고 차세대 세포주 개발을 위해 세포엔지니어링이 절대적으로 필요하다. 효과적인 동물 세포엔지니어링은 유전자의 특성에 따라 발현량과 시기를 정확하게 제어함으로써 구현할 수 있다. 그러나 일시발현이나 무작위 유전자 삽입을 통한 기존의 동물 세포엔지니어링은 정교하지 못하며 지속 가능성이 떨어지는 문제에 직면해 있다. 따라서 이러한 단점을 극복하고 동물 세포 합성 생물학 연구에 사용될 수 있는 플랫폼 기술로서, 신뢰할 수 있는 유도발현 세포주의 개발이 큰 가치가 있을 것으로 기대된다. 본 연구에서는 CRISPR/Cas9과 재조합 효소 매개 카세트 교환 방법 (RMCE)을 통해 다양한 표적 유전자의 발현을 정교하고 지속 가능하게 제어할 수 있는 독시사이클린 유도 발현 세포주 개발법을 확립하였다. 또한 사례 연구를 통해 그 유용성과 가치를 입증하였다. 효과적인 동물세포 엔지니어링의 또 다른 중요한 요소는 환경과 맥락에 따른 적절한 표적 단백질을 선별하는 것이다. 하지만 이전에 지식 또는 오믹스/예측에 기반하여 효과를 보였던 표적 단백질들은 불완전한 데이터와 맥락에 따라 재현성과 효과가 제한적일수 있다. 따라서 본 연구에서는 두 초세포주에서 RMCE 매개 전장 CRISPR 녹아웃 스크리닝을 수행하여, 유전자의 기능을 이해하고 신규 타겟을 발굴하고자 하였다. 결과적으로, 차세대 염기서열 분석을 통해 얻은 데이터를 활용하여 라이브러리 내 가이드 RNA 분포를 상호 비교하였으며, 핵심 또는 조건에 따른 필수유전자 및 바이오 의약품 생산에 관한 이로운 표현형을 보이는 표적 유전자들을 선별하였다. 해당 기술을 통해 얻어낸 데이터는 신뢰 및 재현 가능하며, 난발현 단백질 생산과 같은 다양한 표현형에 부합하는 새로운 타겟을 발굴하는데 활용될 수 있음을 검증하였다. 본 연구에서 CRISPR과 RMCE기술로 개발된 (다중) 위치 특이적 유전자 삽입, 신뢰 가능한 유전자 발현조절, 그리고 전장 유전체 녹아웃/기능 유전체학 기반의 엔지니어링 플랫폼은 재조합 초세포주의 생산성을 증대하고 후보 신약의 검증 및 대량 생산 기간을 혁신적으로 단축시켜, 향후 증가할 의료수요 충족에 기여할 것으로 기대된다.
학위논문(박사)--분자과학기술학과,2024. 8
Keywords: CRISPR; Cell engineering; Chinese hamster ovary; RMCE; Site-specific integration